Customer Experience, Customer Engagement, and Social Media Advertising on Customer Loyalty: The Mediating Role of Customer Satisfaction at Bu Rudy Surabaya - Faradilah Trixie Agrilya; Nuri Purwanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The Indonesian souvenir industry, especially culinary-based small and medium enterprises, continues to grow in response to rising tourism activity. limited research integrates customer experience, customer engagement, and social media advertising within a single model to explain consumer loyalty, particularly while examining the mediating role of customer satisfaction. This study addresses that gap by investigating how these three marketing variables influence loyalty, customer satisfaction serving as the intervening factor, using Bu Rudy Surabaya as the research context. A quantitative (associative) design was applied, involving 100 respondents selected through convenience sampling. Data were processed using SmartPLS to evaluate both measurement and structural components. The findings reveal that customer experience and customer engagement enhance customer satisfaction, which then mediates their impact on loyalty. Social media advertising does not generate a significant effect on either satisfaction or loyalty. Customer experience emerges as the most influential determinant of consumer responses. The study offers an integrated empirical perspective on consumer behavior in culinary-based small and medium enterprises and provides practical recommendations for improving loyalty through strengthened experiences and meaningful customer engagement.